2021
DOI: 10.21037/jtd-20-2267
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of robot assisted thoracic surgical resection of non-small cell lung cancer: nodal upstaging and mediastinal recurrence

Abstract: Background: Robot assisted thoracic surgery (RATS) is the minimally invasive surgical technique of choice for treatment of patients with non-small cell lung cancer (NSCLC), at the Isala Hospital. The aim of this study is to compare clinical and pathological staging results and mediastinal recurrence after RATS for anatomical resections of lung cancer as surrogate markers for quality of mediastinal lymph node dissection (MLND). Methods: This single institute retrospective study was conducted in patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, nodal upstaging has a significant prognostic impact. Basically, this retrospective study regarding the oncological outcomes of robotic surgery at our department demonstrated similar results to the ones previously described [33].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, nodal upstaging has a significant prognostic impact. Basically, this retrospective study regarding the oncological outcomes of robotic surgery at our department demonstrated similar results to the ones previously described [33].…”
Section: Discussionsupporting
confidence: 85%
“…This is the first study investigating the advantages and disadvantages of RATS and VATS in NSCLC patients with different BMI ranges. The best surgical option for resectable stage II and above NSCLC is still controversial, and studies generally agree that thoracotomy can achieve excellent long-term postoperative outcomes, especially in lymph node dissection (13,19). It has been reported recently that RATS has the same long-term outcomes as thoracotomy and VATS, as well as better short-term results (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The technical features of the robot platform are valuable, especially in challenging lymph nodes, such as the ones that are adherent to arteries or the subcarinal nodes in left sided cases. The value of RATS in lymph node dissection is further elaborated in our recently published article [24].…”
Section: Lymph Node Dissectionmentioning
confidence: 99%